2021
DOI: 10.3390/foods10081951
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Differentiation of Hom Mali Rice Cultivated in Different Regions of Thailand Using FTIR-ATR and NIR Spectroscopy

Abstract: Although Hom Mali rice is considered the highest quality rice in Thailand, it is susceptible to adulteration and substitution. There is a need for rapid, low-cost and efficient analytical techniques for monitoring the authenticity and geographical origin of Thai Hom Mali rice. In this study, two infrared spectroscopy techniques, Fourier-transform infrared spectroscopy with attenuated total reflection (FTIR-ATR) and near-infrared (NIR) spectroscopy, were applied and compared for the differentiation of Thai Hom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The use of a low-cost and portable NIR spectroscopy technique to discriminate between Thai jasmine rice grown in different regions of Thailand has been recently reported by Srinuttrakul et al [43]. It is shown that the proposed method is reliable in detecting the geographical origin of jasmine rice samples from two cultivation regions, northern and northeastern, which could be further used as a screening method to detect rice fraud related to geographical origins.…”
Section: Resultsmentioning
confidence: 91%
“…The use of a low-cost and portable NIR spectroscopy technique to discriminate between Thai jasmine rice grown in different regions of Thailand has been recently reported by Srinuttrakul et al [43]. It is shown that the proposed method is reliable in detecting the geographical origin of jasmine rice samples from two cultivation regions, northern and northeastern, which could be further used as a screening method to detect rice fraud related to geographical origins.…”
Section: Resultsmentioning
confidence: 91%
“…Compared with conventional detection methods, near-infrared spectroscopy technology has advantages such as fast detection speed, multi-component detection, and non-destructive testing. However, there are differences in quality between different rice varieties in different production areas [36] , and the model established by the same indicator cannot be fully applicable to different rice products, resulting in poor universality. Compared with near-infrared spectroscopy technology, machine vision technology can extract color features, texture features, and other information from sample images [37] .…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…In the PGI origin discrimination of this study based on the HSI full wavelength, the OPLSDA model was suitable for pairwise comparison of origin traceability. Meanwhile, the good results in region discrimination by using the OPLSDA model from previous reports were listed, including Thai Hom Mali rice traceability ( 39 ) as well as the origin prediction of Huangjing from the PGI regions of Qingyang City, China ( 40 ).…”
Section: Discussionmentioning
confidence: 99%